PERAN TOKOH MASYARAKAT DALAM MEMBANTU MENJALANKAN PROGRAM KKN - Naser, Muhammad Nikman; Ardi, Hervin; Bella, Arjeni; Mella, Reza; Yolla Ardian, Rini Syerliana; Mardanti, Lenia (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
Real Work Lecture Activities (KKN) is an educational approach that provides students with practical learning experiences in communities outside campus. This service aims to carry out the KKN program in Pasar Ngalam Village, Kec. District fish water. Seluma. The KKN program carried out by UIN Fatmawati Sukarno Bengkulu students lasts for one month, namely from 19 July to 3 August 2024. This service uses observation and interview methods to collect data from community leaders, teachers and students. As for the results of data analysis, it was found that KKN activities created programs by assisting activities in Pasar Ngalam Village, Kec. District fish water. All in terms of religion, education and culture. The activity program in terms of education includes holding lessons at the KKN post which is attended by children from Pasar Ngalam Village, Kec. District fish water. Seluma. The religious activity program carried out by KKN students is (1) creating an event commemorating the 1st of Muharram which is packaged through a coloring competition, short verse competition, fashion show, and the call to prayer which is attended by children from kindergarten to grade 6 elementary school, (2) establishing RISMA, (3) Teaching the Koran at the TPQ in the mosque in Pasar Ngalam village, sub-district. District fish water. Seluma, (4) Participating in Yasinan every Friday night with the village residents which is held at the mosque, (5) Cleaning the village mosque with RISMA. Meanwhile, the social activity program carried out by KKN students is holding gymnastics with village PKK women and participating in Posyandu activities at the Village Hall. Of all the activity programs carried out by KKN students, they are the result of discussions with community leaders, village officials, teachers and residents and have been approved by all parties. In implementing the KKN activity program, there is an important role for community leaders and all parties in the village in coordinating and guiding all activities, thereby producing a program that can build a better village. The results of the activity program that has been implemented show that KKN has had a positive impact on community development starting from active religious activities in mosques, increasing awareness of the importance of education, and increasing socialization with one another. Overall, this service highlights the potential of KKN programs in encouraging community development and realizing synergistic community relations.